Standards as Hybrid Forum: Comparison of the Post-Fukushima Radiation Standards by a Consumer Cooperative, the Private Sector, and the Japanese Government - Hirata Kimura, Aya (The International Journal of Sociology of Agriculture and Food, 2013)
Many have critiqued private food standards as neo-liberalization that reduces the power of government. However, a growing body of literature suggests that government standards do not necessarily result in better outcomes. In fact, some private standards can play a role in the construction of what feminist theorist Nancy Fraser calls ‘counterpublics’, which play an important role in holding the government accountable in late capitalist society. Callon et al.’s notion of a ‘hybrid forum’ is useful in theorizing this democratizing potential of standards. A ‘hybrid forum’ is a space to discuss techno-scientific matters that includes both laypeople and experts, and Callon et al. suggest six criteria (equality, transparency, clarity, intensity, openness, and quality) for judging the degree to which a hybrid forum achieves a democratic discussion on techno-scientific issues. The article uses these criteria to evaluate three standards (government, private sector, and a consumer cooperative called Seikatsu Club Consumer Cooperative or SCCC) that are emerging in response to contamination of food by radioactive materials in the aftermath of the Fukushima nuclear power plant disasters in Japan. The article finds that the corporate and government standard-setting processes failed to offer meaningful opportunities for democratic debate in comparison with SCCC’s process. The broader theoretical implication of the article is that democratic dialogue is an important aspect of the process of setting food standards, and it should be taken into consideration when the worth of various food standards is evaluated.